Novel mixed-method, inclusive protocol involving global key stakeholders, including carers as experts, to co-develop relevant Caregiver-Reported Outcome Domains (CRODs) in skin disease - Anthony Bewley; Fiona Browne; Alan D Irvine; Gerard Leavey; Amy S Paller; Jemima E Mellerio; Carleen Walsh; Marian Mc Laughlin (BMJ Open, 2023)
Introduction Ichthyoses comprise a heterogenous group of rare genetic skin disorders that involves the entire skin surface, often with additional syndromic features, and pose many clinical challenges. Without curative intervention, the mainstay of life-long symptom management is supportive in nature and can remain the responsibility of the caregiver. Although impact on the wider family is considered an important outcome of policies and services, there is a lack of caregiver consensus on what outcome domains to measure to fully assess the impact of ichthyosis on the patient and the caregiver. This project aims to identify a set of core outcome domains towards a core outcome set for ichthyosis that can measure all relevant concepts of ichthyosis in clinical practice, service delivery and research.Methods and analysis Following the COMET (Core Outcome Measures in Effectiveness Trials) initiative, this project will employ a mixed-method study design which was developed using public and patient involvement and an international multidisciplinary expert group (clinical experts, patients and their representatives, policymakers, researchers and service providers). Experts by experience, or caregivers, will be recruited through online ichthyosis support groups. Phase one will focus on item generation and involve: (1) a systematic literature review, (2) a multimethods international qualitative study with ichthyosis caregivers and (3) co-development of items for an e-survey. Phase two, item refinement, will employ a novel four-pronged consensus approach: (1) an e-Delphi survey, (2) statistical analysis of e-Delphi survey results, (3) online qualitative feedback and (4) an online consensus discussion. All methodological considerations will be clearly linked with each Core Outcome Set-STAndards for Developing recommendation.Ethics and dissemination Research Ethics Committee approval obtained from the School of Psychology, Ulster University (UK)(Ref:REC/20/0004). Results will be presented in published international peer-reviewed journals, at scientific meetings and support groups.Registration COMET database (January 2019).